2011
DOI: 10.2140/agt.2011.11.2971
|View full text |Cite
|
Sign up to set email alerts
|

Reducible braids and Garside Theory

Abstract: We show that reducible braids which are, in a Garside-theoretical sense, as simple as possible within their conjugacy class, are also as simple as possible in a geometric sense. More precisely, if a braid belongs to a certain subset of its conjugacy class which we call the stabilized set of sliding circuits, and if it is reducible, then its reducibility is geometrically obvious: it has a round or almost round reducing curve. Moreover, for any given braid, an element of its stabilized set of sliding circuits ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Finally we recall the two following results from [27]: Theorem 5.16). Let x ∈ B n be a non-periodic, reducible braid which is rigid.…”
Section: 3mentioning
confidence: 87%
See 3 more Smart Citations
“…Finally we recall the two following results from [27]: Theorem 5.16). Let x ∈ B n be a non-periodic, reducible braid which is rigid.…”
Section: 3mentioning
confidence: 87%
“…In [27], González-Meneses and Wiest showed that every element of (some refined version of) the set of Sliding Circuits of a reducible braid preserves a family of round or almost-round curves.…”
Section: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper is a branch of the paper [10], and I am extremely grateful to Juan González-Meneses for many helpful discussions.…”
mentioning
confidence: 99%